Seasonal habitat use and movements of woodland caribou in the Omineca Mountains, north central British Columbia, 1991-1993 - Wood, Mari D. (Rangifer, 1996)
From 1991 to 1993, 30 woodland caribou were captured and fitted with radio-collars west of the Williston Reservoir in north central B.C. Monthly radio-telemetry location flights revealed that caribou in the Northern Area, characterized by a complex of mountain ranges, moved greater distances to calving areas than did those in the South, where only one major mountain range exists. In the year of record heavy snowfall for the area, all collared caribou wintered on windswept alpine slopes, while during the below average snowfall year, many caribou remained in forested habitats. In winter, caribou were found to forage on terrestrial lichens in both lowland lodgepole pine flats and on windswept alpine slopes, and on arboreal lichens in upper elevation Engelmann spruce and subalpine fir forests. There are at least 600-700 caribou in the Omineca Mountains.
Keywords: Rangifer; woodland caribou; snow depths; mortality; population dynamics; habitat use; migration; Omineca; British Columbia